2013
DOI: 10.1162/jocn_a_00306
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Correlates of Motor and Working Memory Performance following Subthalamic Nucleus Stimulation

Abstract: Subthalamic nucleus (STN) deep brain stimulation (DBS) has become an accepted treatment for the motor manifestations of Parkinson disease (PD). The beneficial motor effects of STN DBS are likely due to modulation of BG output to frontal cortical regions associated with motor control, but the underlying neurophysiology of STN DBS effects, especially at the level of the cortex, is not well understood. In this study, we examined the effects of STN DBS on motor disability and visual working memory, a cognitive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Stimulation generally has not demonstrated an effect on ERP latency. Only one study (Selzler et al 2013) has reported a slowing in latency to match that of the control group, although task performance did not change. The lack of correlation between task performance and ERP generation suggests that more sophisticated measures are required to assess the effects of DBS, a point directly demonstrated by Swann et al (2011), where time-frequency plots showed greater sensitivity to the effects of DBS whereas ERPs were insensitive to these effects.…”
Section: Network Effects Of Subthalamic Nucleus Stimulationmentioning
confidence: 95%
“…Stimulation generally has not demonstrated an effect on ERP latency. Only one study (Selzler et al 2013) has reported a slowing in latency to match that of the control group, although task performance did not change. The lack of correlation between task performance and ERP generation suggests that more sophisticated measures are required to assess the effects of DBS, a point directly demonstrated by Swann et al (2011), where time-frequency plots showed greater sensitivity to the effects of DBS whereas ERPs were insensitive to these effects.…”
Section: Network Effects Of Subthalamic Nucleus Stimulationmentioning
confidence: 95%
“…At the time of this writing, it has been publicly available for three years, and the latest version is 4.0. It is stable and reliable, has been downloaded over 7000 times, and has been used in many published papers that examine a broad variety of topics (e.g., Lawhern et al, 2012; Nemrodov and Itier, 2012; Sawaki et al, 2012; Beckes et al, 2013; Leonard et al, 2013; Selzler et al, 2013; Strauss et al, 2013). …”
Section: Concluding Commentsmentioning
confidence: 99%
“…For example, a randomized, controlled trial of bilateral STN and globus pallidus internus (GPi)-DBS vs best medical treatment found that DBS patients experienced small decrements on measures of WM, processing speed and visual delayed recall 33. Selzler et al34 examined the effects of STN-DBS on motor disability and visual WM, with participants in the Med-OFF condition and DBS-ON or DBS-OFF, and concluded that DBS improved clinical motor function but had little effect on WM performance. Whereas some STN-DBS and GPi-DBS studies have reported WM improvements after treatment,9,10 others have shown either no change35 or worsening of WM 11,36.…”
Section: Discussionmentioning
confidence: 99%